Morphometry of Cortical Neurons in Acute Clozapine and Ethanol Poisoning - A. R. Bashirova; D. V. Sundukov; A. S. Babkina; M. A. Golubev; I. N. Telipov (Общая реаниматология, 2020)
The aim of the study is to summarize the histology and morphometry of cortical neurons in acute clozapine and ethanol poisoning.Material and methods. Histological examination of the parietal cortical brain samples of 26 patients died during the Day 1 of acute clozapine and ethanol poisoning (23 males and 3 females aged 22-63 years) was performed. The blood ethanol level was 1.4-4.1%o. The level of clozapine in the blood ranged between 0.24 and 5.8 mg%, in the liver between 0.097 and 6.5 mg%, in kidneys between 0.03 and 3.5 mg%. The cortical samples for morphometric examination were placed in 10% neutral paraformaldehyde, the histological sections were done and stained with hematoxylin and eosin, as well as according to Niessl. The morphological analysis was performed using the video light microscopy. The number of damaged neurons (with separate quantification of reversible, intermediate, and irreversible damage) was assessed. The statistical analysis was done using the non-parametric methods.Results. The signs of brain neuronal damage in acute clozapine and ethanol poisoning, as well as forensic chemical tests, might be used for establishing the direct cause of death.